Pengaruh Tingkat Suku Bunga, Nilai Tukar Rupiah dan Jumlah Ekspor Terhadap Tingkat Kredit PERBANKAN - Yoda Ditria; Jenni Vivian; Indra Widjaja (Journal of Applied Finance & Accounting, 2008)
Interest rates level, exchange rates value and the export quantity are the variables of macroeconomy that always change according to the economic condition of a nation. A good knowledge about the effect of these three variables towards the amount of lending by banks, which consists of three kinds: working capital loan, investment loan, and consumption loan, will help banks’ strategic plan to face the economic volatility. Bank is a financial institution that serves as a bridge between parties that have excess funds with parties that need some funds. Banks are expected to provide loans to the public to sustain economic growth with prudence to reduce the risks, which can be customer risks or systemic risks. The goal of this research is to study the effects and relationship between interest rates level, exchange rates movement, and export quantity towards the credit level of banks and also the three kinds of bank loans, which are the working capital loan, investment loan and consumer loan using historical data from Quarter I 2002 to Quarter III 2007. The result of research indicates that the macroeconomic variables above affect the amount of lending and the three kinds of loan: working capital loan, investment loan and consumer loan. The result also shows that although the three macroeconomic variables have the same influence towards the three kinds of loan, the magnitude of the influence towards each kind of loan is different, in which the investment loan has a big influence towards the interest rates level change, working capital loan has a big influence towards the export quantity and exchange rates, and consumer loan has a moderate influence towards the variation of the three macroeconomic variables.